Analisis Dampak Telekonseling Kebidanan terhadap Kecemasan Ibu Hamil Menjelang Persalinan - Dewi Parwati; Larasuci Arini; Susilawati Susilawati; Sulfiana Sulfiana; Risma Putri Utama; Rezqiqah Aulia Rahmat (Barongko: Jurnal Ilmu Kesehatan, 2026)
Background: As labor approaches, many pregnant women experience anxiety, which can affect the delivery process and the health of both mother and fetus. Midwifery telecounseling is an innovative maternal health service that allows pregnant women to receive education, emotional support, and remote monitoring. Objective: This study aims to analyze the impact of midwifery telecounseling on the anxiety levels of pregnant women approaching labor. Methods: This study used a quasi-experimental design with a pretest-posttest and a control group. The sample consisted of 60 pregnant women in their third trimester, divided into an intervention group (n=30) receiving midwifery telecounseling for 4 weeks, and a control group (n=30) receiving routine care. Anxiety levels were measured using the Pregnancy-Related Anxiety Questionnaire (PRAQ) before and after the intervention. Data were analyzed using paired t-tests and independent t-tests. Results: The study showed that pregnant women who received midwifery telecounseling experienced a significant reduction in anxiety scores (pretest 35.6 ± 5.2; posttest 28.3 ± 4.7; p < 0.001), while the control group showed no significant change (pretest 34.9 ± 5.0; posttest 33.8 ± 5.1; p = 0.182). A posttest comparison between the intervention and control groups showed a significant difference (p < 0.001). Conclusion: Midwifery telecounseling effectively reduced maternal anxiety levels prior to delivery. Implementation of telecounseling services can be an important strategy in modern midwifery care.